2018
DOI: 10.1371/journal.pone.0195029
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Bayesian 2-test case: The effect of tree diagrams on medical decision making

Abstract: In medicine, diagnoses based on medical test results are probabilistic by nature. Unfortunately, cognitive illusions regarding the statistical meaning of test results are well documented among patients, medical students, and even physicians. There are two effective strategies that can foster insight into what is known as Bayesian reasoning situations: (1) translating the statistical information on the prevalence of a disease and the sensitivity and the false-alarm rate of a specific test for that disease from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 60 publications
2
37
0
Order By: Relevance
“…The results of the study could reveal that the developed visualization software allows verifying the patient's case in an appropriate timeframe and reducing the probability of inexact (non-helpful) data due to an improved transparency and verifiability [12,48]. Overall, this approach presented the technical feasibility and also the possible clinical integration of digital patient models for supporting therapy decision making in (preoperative) interdisciplinary tumor boards based on Bayesian Networks, which is also confirmed in the literature [62][63][64].…”
Section: Digital Patient and Process Modelssupporting
confidence: 53%
“…The results of the study could reveal that the developed visualization software allows verifying the patient's case in an appropriate timeframe and reducing the probability of inexact (non-helpful) data due to an improved transparency and verifiability [12,48]. Overall, this approach presented the technical feasibility and also the possible clinical integration of digital patient models for supporting therapy decision making in (preoperative) interdisciplinary tumor boards based on Bayesian Networks, which is also confirmed in the literature [62][63][64].…”
Section: Digital Patient and Process Modelssupporting
confidence: 53%
“…In the meta-analysis by McDowell and Jacobs (2017), frequency versions of Bayesian reasoning problems can be solved on average by 24% of participants across studies and contexts. Even in more complex Bayesian problems, such as in situations involving more than one medical test or unclear test results, frequencies help people in their decision-making processes (Hoffrage et al, 2015b; Binder et al, 2018). In the last 20 years, an abundance of studies has shown the facilitating effect of frequencies for many different kinds of populations: physicians, patients, judges in court, managers, university and high school students, and even young children (Gigerenzer and Hoffrage, 1995; Hoffrage et al, 2000; Zhu and Gigerenzer, 2006; Siegrist and Keller, 2011; Hoffrage et al, 2015a; McDowell and Jacobs, 2017).…”
Section: Statistical Thinkingmentioning
confidence: 99%
“…The tasks are difficult for medical students and easy for math students. The task itself has a certain degree of complexity (1-test-case=simple/non-complex and 2-test-cases=complex), the probability of solution and thus the difficulty depends on the recipient [8]. The pre-knowledge of the person trying to solve the task influences the level of difficulty much more than the complexity does.…”
Section: Introductionmentioning
confidence: 99%